Lyndon Johnson's war : America's cold war crusade in Vietnam, 1945-1968 - Hunt, Michael H. (New York : Hill and Wang, 1996)
The Vietnam War, perhaps the mast controversial war Americans have ever fought, remains a source of pain and perplexity. Why did Lyndon Johnson commit the United States to fight? Why did he fail to act more decisively once he resolved on war? And why didn't he take the American public into his confidence? These questions have troubled historians since the end of the war, but the answers have been buried in inaccessible documents. Now Michael H. Hunt uses newly available sources from both American and Vietnamese archives to reevaluate how and why the war started and then escalated. He examines the ideological, strategic, political, and institutional pressures that in the 1950s propelled the Truman and Eisenhower administrations toward intervention in Indochina; the reasons why Kennedy's and Johnson's policymakers believed that a limited war could be fought there; Johnson's early position on Vietnam and his decision to intensify U.S. involvement in the war; and, finally, the tragic consequences of the Vietnam War both at home and abroad. Throughout, he discusses the values, choices, misconceptions, and miscalculations that shaped the long process of American intervention, thus rendering more comprehensible - if no less troubling - the tangled origins of the Vietnam War.
The Cold War world of The Ugly American -- Ho Chi Minh's brocade bags -- Learned academics on the Potomac -- "That bitch of a war" -- How heavy the reckoning?
Includes bibliographical references (p. [133]-139) and index.
Keywords: Johnson, Lyndon B. -- 1908-1973.; Vietnam War, 1961-1975 -- United States; United States -- Foreign relations -- Vietnam; Vietnam -- Foreign relations -- United States; Vietnam -- History -- 1945-1975.